PERAN DOSEN MATA KULIAH PENDIDIKAN PANCASILA DAN KEWARGANEGARAAN DALAM MENINGKATKAN RASA NASIONALISME MAHASISWA - Toni Anwar Mahmud; Tajudin Hasan (Pendidikan Pancasila dan Kewarganegaraan, FKIP, Universitas Banten Jaya, 2019)
This research is done because the number of students of UNBAJA’s PPKn courses semester II and IV academic year 2017 - 2018 have low nationalism.. This was seen from the results of tests that showed that there were still many students of the UNBAJA’s PPKn courses in the second and fourth semester of the 2017-2018 academic year who did not memorize the Pancasila and Indonesian Raya, and did not understand the meaning of Bhinneka Tunggal Ika. The purpose of this study was to determine the causes of the low sense of nationalism of students in the UNBAJA’s PPKn courses in the second and fourth semester of 2017 - 2018 academic year and to find out the role of lecturers of PPKn courses in increasing the nationalism feeling of students in the UNBAJA’s PPKn courses in the second and fourth semester of 2017 - 2018. This study uses a descriptive method of qualitative approach with data collection techniques using test techniques, observation and interviews. Subjects of this study are lecturers of UNBAJA’s PPKn courses and students of UNBAJA’s PPKn courses in second and fourth semester of academic year 2017 - 2018. The results of this study indicate that the role of the PPKn lecturer can increase the sense of nationalism of students in the PPKn UNBAJA courses in the second and fourth semester of the 2017 - 2018 academic year, such as before the teaching and learning activities are conducted in class, the lecturer always instructed everyone to pray.